2020
DOI: 10.33019/society.v8i1.134
|View full text |Cite
|
Sign up to set email alerts
|

CSR Partnership Model for Sustainable MSMEs Development: A Case Study of the Partnership Program at PT Jasa Marga (Persero) Tbk

Abstract: This research aims to examine Corporate Social Responsibility (CSR) Partnership Program to find an optimal and sustainable partnership model between State-owned Enterprises (SOEs) and Micro Small and Medium Enterprises (MSMEs) to advance the people's economic sector. This research was qualitative research with a case study approach. Data collection techniques used in this research were in-depth interviews, observation, and literature studies. In-depth interviews were conducted with 3 informants chosen as repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Another study conducted research on the CSR programs of a large company in Indonesia from 1980 to 2011 and revealed that the large company played a role in enhancing the capabilities of micro-business owners and workers involved in the company's supply chain [30]. The positive impact of implementing CSR programs, as demonstrated by this study, has also been substantiated by studies [23,51,52]. Nevertheless, the significant impact of CSR on the performance of micro-enterprises cannot be separated from the entrepreneurial attitude exhibited by these micro-enterprise actors [13].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Another study conducted research on the CSR programs of a large company in Indonesia from 1980 to 2011 and revealed that the large company played a role in enhancing the capabilities of micro-business owners and workers involved in the company's supply chain [30]. The positive impact of implementing CSR programs, as demonstrated by this study, has also been substantiated by studies [23,51,52]. Nevertheless, the significant impact of CSR on the performance of micro-enterprises cannot be separated from the entrepreneurial attitude exhibited by these micro-enterprise actors [13].…”
Section: Resultssupporting
confidence: 66%
“…It reflects a growing recognition that companies have a responsibility not only to shareholders but also to the broader global community, society, and the planet. ESR is driven by a combination of ethical considerations, stakeholder expectations, regulatory frameworks, and the recognition that responsible business practices contribute to long-term profitability and sustainability [23].…”
Section: Environmental Social Responsibility In Its Legal and Global ...mentioning
confidence: 99%